2020
DOI: 10.1080/1360144x.2020.1762087
|View full text |Cite
|
Sign up to set email alerts
|

Imposter syndrome and the accidental academic: an autoethnographic account

Abstract: In this paper I use an autoethnographic approach to explore my everyday experiences as an early career lecturer at a UK-based university. I uncover some of my underlying experiences of Imposter Syndrome, presenting the ways Imposter Syndrome manifests in my teaching activities. This paper recommends areas in which Higher Education Institutions can offer support to early career academics, for instance through mentoring/training in: dealing with nerves; classroom behaviour management; and dressing for confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Whilst most of the literature emphasises the positive outcomes of conference attendance Orland-Barak and Tillema ( 2006) point out that there are downsides too such as teachers feeling intimidated by highly experienced researchers or considering that they have nothing to offer. Wilkinson (2020) has also shown that 'imposter syndrome' can inhibit the learning that could take place in conferences. Our findings indicate that teachers' attendance at a professional conference in a subject within their field of professional interest and expertise ultimately mitigated against feelings of low self-confidence.…”
Section: Conferences and Professional Developmentmentioning
confidence: 99%
“…Whilst most of the literature emphasises the positive outcomes of conference attendance Orland-Barak and Tillema ( 2006) point out that there are downsides too such as teachers feeling intimidated by highly experienced researchers or considering that they have nothing to offer. Wilkinson (2020) has also shown that 'imposter syndrome' can inhibit the learning that could take place in conferences. Our findings indicate that teachers' attendance at a professional conference in a subject within their field of professional interest and expertise ultimately mitigated against feelings of low self-confidence.…”
Section: Conferences and Professional Developmentmentioning
confidence: 99%
“…More recently, and perhaps partly as a result of this 'fuzziness' around the academic developer role, topics relating to the work conditions of academics are increasingly raised in IJAD. Wilkinson's (2020) frank account of imposter syndrome for early academics in this issue is a good example. Unfortunately, there is an increasing need for a focus on the well-being and health of academic staff as we need to find solutions for sustainable work conditions and practices for individuals, which applies to academic development as well.…”
Section: Topics With Continuing Relevancementioning
confidence: 99%
“…Adaptations of well-established theories or concepts, like Taylor et al's (2020) adaptation of Chickering and Gamson (1987) to extrapolate seven principles for good practice in midterm student feedback, are a not uncommon approach. Both Hunter's (2020) and Wilkinson's (2020) papers are autoethnographic-an approach used to give voice to the lived experience of academic development-and both use metaphor to discuss issues such as imposter syndrome and perceived lack of agency in the construction of one's own professional identity as an academic developer. Furthermore, MacFayden, English, and Coates (2020) use action research to explore the collective experience of supervisors, while Cunningham and Mills (2020) employ a creative methodology and explore academic development through the use of metaphor and poems.…”
Section: Increasing Focus In the Use Of Theory And Empirical Datamentioning
confidence: 99%
“…She explained that I needed to gain my PhD to obtain ongoing employment in a competitive sector of the workforce. However, I soon realised that Academic workloads are substantial, involving teaching, cultivating collaborations, research, meetings as well as substantial academic administration leaving little time for study, let alone production of publications, and maintaining regular contact with your HDR supervisors [1].…”
Section: Contextmentioning
confidence: 99%
“…However, at times I felt lost and felt unsure of my new HDR student role. My 'imposter syndrome self' reared its head and the experience of studying became a battle or hurdle marred by bouts of perfectionism [3], [1].…”
Section: While Working On My Thesis I Used the Gibbs' Six Stage Modelmentioning
confidence: 99%